Aphrodisiacs, Fertility and Medicine in Early Modern England - Jennifer Evans (Royal Historical Society, 2014)
Miss Bland, Wardour Street, Soho. ‘This is a gay volatile girl; very genteel in her person; and has an extraordinary titillation in all her members; which she is very fond of increasing, by making use of provocatives for that purpose such as pullets, pigs, veal, new-laid eggs, oysters, crabs, prawns, eringoes, electuaries, &c. &c. – She is reported to have a kind of savage joy in her embraces, and sometimes leaves the marks of her penetrating teeth on her paramour’s cheeks.’